(untitled) (International Journal of Biomedical Research, 2016)
Background: Impairment of vision can adversely impact the patients quality of life and negatively affect the family dynamic. However, evaluation of the implications of visual impairment on the patients family is often overlooked. Objectives: To summarize the impacts of visual impairment on the patients quality of life and to explore the negative implications of visual impairment on the patients family dynamic. Methods: Electronic Medline database search was conducted between 1946 and 2015 to evaluate the impacts of visual impairment on the quality of life and its effects on the patients family functioning and relationship. The search was restricted to articles published in English and adult more than 18 years old. The initial 80 articles were reviewed and 16 relevant studies were selected in this analysis. Results: Twelve studies assessed the impact of visual impairment on the patients quality of life. Four studies investigated the effects of visual impairment on the patients family dynamic. Visual impairment has negative impacts on different aspects of life including social, psychological, and physical health. Family functioning and relationship can be severely influenced by visual impairment. Conclusion: Assessment of family functioning is crucial in the evaluation of visually impaired patients. Enhancement of adaptation in patients with visual impairment can be accomplished when working with patients and their families.